ANALISIS FAKTOR RISIKO KEJADIAN PENYAKIT GASTRITIS DI WILAYAH KERJA PUSKESMAS WAWOTOBI KABUPATEN KONAWE TAHUN 2020 - Andi Ulfryda Dwi Riwansyah; La Ode Muhamad Sety; WaOde Salma (FKM Universitas Halu Oleo, 2022)
Gastritis is an inflammation of the gastric mucosa that results in swelling of the gastric mucosa until the epithelium is released. The incidence of Gastritis in the world is estimated to affect more than 1.7 billion people. This study aims to analyze the risk factors of diet, stress and economic status of Gastritis disease incidence in patients in the working area of Puskesmas Wawotobi Konawe District in 2020. This study used a case control study design.The population in this study were all patients who checked themselves at The Public Poly of Wawotobi Health Center Konawe Regency in January to August 2020. The samples in this study were 104 samples (52 cases and 52 controls). Sampling using probability sampling technique by means of simple random sampling. The results showed risk factors for Gastritis disease, namely diet obtained p-value = 0,000, OR = 5,127 (CI 95% 2,218-11,850) and stress obtained p-value = 0.000, OR = 4,632 (CI 95% 2,028-10,583), while non-risk factors for Gastritis disease are economic status obtained p-value = 0.554, OR = 1.367 (CI 95% 0.629-2.971). The conclusion is that diet and stress are risk factors and economic status is not a risk factor for Gastritis disease in patients in the working area of Puskesmas Wawotobi Konawe District in 2020. People are expected to always maintain health by conducting clean and healthy living behaviors and also can maintain a balanced diet by applying balanced nutrition.